The dynamic course of psychological outcomes following the Victorian Black Saturday bushfires. (July 2021) - Bryant, Richard A; Gibbs, Lisa; Colin Gallagher, H; Pattison, Phillipa; Lusher, Dean; MacDougall, Colin; Harms, Louise; Block, Karen; Ireton, Greg; Richardson, John; Forbes, David; Molyneaux, Robyn; et al.
Objectives: To profile the long-term mental health outcomes of those affected by the 2009 Black Saturday bushfires and to document the course of mental health since the disaster. Method: The longitudinal Beyond Bushfires study included 1017 respondents (Wave 1; 3–4 years after the fires), 736 (76.1%) at Wave 2 (5 years after the fires) and 525 (51.6%) at Wave 3 (10 years after the fires). The survey indexed fire-related and subsequent stressful events, probable posttraumatic stress disorder, major depressive disorder, alcohol use, severe distress and receipt of health services for mental health problems. Results: Relative to their status 3–4 years after the fires, there were reduced rates of fire-related posttraumatic stress disorder (6.2% vs 12.2%), general posttraumatic stress disorder (14.9% vs 18.7%) and severe distress (4.4% vs 7.5%) at 10 years. There were comparable rates between Wave 1 and Wave 3 for depression (10.9% vs 8.3%) and alcohol abuse (21.8% vs 18.5%). Of people in high-affected regions, 22.1% had posttraumatic stress disorder, depression or severe distress at Wave 3. One-third to one-half of participants who reported probable posttraumatic stress disorder or depression at any assessment did not display the disorder at the next assessment. Worsening of mental health at Wave 3 was associated with the extent of property loss, exposure to recent traumatic events or recent stressful life events. Only 24.6% of those with a probable disorder had sought professional help for this in the previous 6 months. Conclusion: Approximately one-fifth of people from high-affected areas have a probable psychological disorder a decade after the fires. Mental health appears to fluctuate for those who are not consistently resilient, apparently as a result of ongoing stressors. The observation that most people with probable disorder are not receiving care highlights the need for further planning about managing long-term mental health needs of disaster-affected communities.